Epidemiology of Diseases of Cultured Black Tiger Shrimp (Penaeus Monodon) In Peninsular Malaysia and Experimental Inactivation of White Spot Syndrome Virus - Wang, Yin Geng (2001)
A large-scale investigation for detection of shrimp diseases was carried out from 1994 to 1999. Cultured Penaeus monodon, were collected from 26 hatcheries and 58 growout farms in 10 states along the coast of Peninsular Malaysia. Six viruses were identified, namely monodon baculovirus (MBV), white spot syndrome virus (WSSV), hepatopancreatic parvovirus (HPV), baculoviral midgut gland necrosis (BMNV), yellow-head virus (YHV) and infectious hypodermal and hematopoietic necrosis virus (IHHNV). Penaeus monodon cytoplasmic giant body (PmCGB) was a newly recognized inclusion with unknown aetiology. With the exception of MBV, this is the first confirmation of the presence of these viruses in the Malaysian shrimp farming systems. With emphasis on viral diseases, the rate of infection (ROI) and severity of infection (Sal) of each disease was evaluated based on the samples pooled for one-year period from 1994 to 1995. The postlarvae were determined to be infected with MBV with prevalence of 33%, YHV 52% and PmCGB 80%. While in growout, the subadults' prevalence of viral infection was as follows; MBV 76%, YHV 76%, WSSV 23%, BMNV 18%, IHHNV 8%, HPV 3%, and PmCGB 99%. The prevalence of MBV had increased 46% from 1988 to 1994, while the prevalence of WSSV from 23% in 1994 to 80% in the end of 1996. Other diseases detected were parasitic diseases, including epicommensal ciliates, gregarine and microsporidian; fungal disease was mainly manifested by larval mycosis; bacterial diseases such as filamentous bacterial disease, antennal deformity syndrome, brown spot, red leg, tail rot, luminous disease, bacterial septicaemia, and two newly recognized bacterial diseases named as bacterial white spot syndrome (BWSS) and soft body-white feces syndrome (SBWFS). BWSS was associated with Bacillus sub tilis, and SBWFS was related to Vibrio alginolyticus, V. parahaemolyticus and Aeromonas hydrophila. For most viral infections, histopathological and ultrastructural studies showed detail pathogenesis and cytopathic effects. The nucleosome of WSSV was described for the first time in the penaeid viruses, and the mechanism of white spot formation caused by WSSV was preliminarily elucidated. All populations examined were found to have multiple infections with viral and other microbial agents. Based on the cytopathic effect of these infections and associated mortality, viruses were regarded as the major disease agent in growout populations. In consideration to their ROI and SOl indices, WSSV, MBV, BMNV, YHV, HPV and PmCGB were categorized as important agents. For hatchery-reared larvae, MBV was the significant pathogen in spite of the fact that bacteria, protozoa and fungi were also recorded to cause mortalities in some cases. White spot syndrome and SBWFS were the most risky diseases causing massive losses to shrimp culture. Infectivity assays on WSSV revealed that the virus could survive ins hrimp carcass for 6 days, and the cell-free WSSV survived in seawater for no longer than 2 days. P. monodon subadults were proved to resist WSSV infection at salinity 2.5 ppt or lower. While ozone at concentration of 0.03 mg/L, formalin at 30 ppm, and calcium oxide at 75 ppm were found to be effective in inactivating WSSV. Povidone iodine at 0 to 15 ppm showed no effect during the viral penetration period. Based on these findings, the control measures and treatment for white spot syndrome were proposed.